Performative agency and incremental change in a CSR context. (April 2020) - Grisard, Claudine; Annisette, Marcia; Graham, Cameron
Abstract: Based on a two-year participant observation, this paper shows how CSR managers align CSR programs closer to their personal convictions and eventually bring about incremental change. We focus on two CSR managers working on a project to develop a business aimed at serving rural West African consumers and show that while they frame their project in financial terms, they incrementally transform the firm's representations in accordance with their own vision of CSR. We deploy Butler's understanding of subjection through performative agency to show that even if CSR managers reproduce the CSR business case discourse to render their actions legitimate and recognizable, this empowers them to exercise a small degree of agency, allowing them to infuse a more inclusive perception of rural low-income populations into the firm's practices. This paper makes two contributions. First, it shows that the subject can incrementally act to transform the dominant financial discourse governing her subjection to better align it with her desire. Second, we establish that the CSR manager navigates between the traditional duo of CSR actors: the organization and its stakeholders and therefore renders porous the boundary between them both.